NVX-CoV2373-induced T- and B-cellular immunity in immunosuppressed people with multiple sclerosis that failed to respond to mRNA and viral vector SARS-CoV-2 vaccines - Mueller-Enz, Magdalena; Woopen, Christina; Katoul Al Rahbani, Georges; Haase, Rocco; Dunsche, Marie; Ziemssen, Tjalf; Akgün, Katja (Frontiers in Immunology, 2023)
Importance Immunological response to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccination is important, especially in people with multiple sclerosis (pwMS) on immunosuppressive therapies. Objective This study aims to determine whether adjuvanted protein-based vaccine NVX-CoV2373 is able to induce an immune response to SARS-CoV-2 in pwMS with inadequate responses to prior triple mRNA/viral vector vaccination. Design, setting, and participants We conducted a single-center, prospective longitudinal cohort study at the MS Center in Dresden, Germany. In total, 65 participants were included in the study in accordance with the following eligibility criteria: age > 18 years, immunomodulatory treatment, and insufficient T-cellular and humoral response to prior vaccination with at least two doses of SARS-CoV-2 mRNA (BNT162b2, mRNA-1273) or viral vector vaccines (AZD1222, Ad26.COV2.S). Interventions Intramuscular vaccination with two doses of NVX-CoV2373 at baseline and 3 weeks of follow-up. Main outcomes and measures The development of SARS-CoV-2-specific antibodies and T-cell responses was evaluated. Results For the final analysis, data from 47 patients on stable treatment with sphingosine-1-phosphate receptor (S1PR) modulators and 17 on ocrelizumab were available. The tolerability of the NVX-CoV2373 vaccination was overall good and comparable to the one reported for the general population. After the second NVX-CoV2373 vaccination, 59% of S1PR-modulated patients developed antispike IgG antibodies above the predefined cutoff of 200 binding antibody units (BAU)/ml (mean, 1,204.37 [95% CI, 693.15, 2,092.65] BAU/ml), whereas no clinically significant T-cell response was found. In the subgroup of the patients on ocrelizumab treatment, 23.5% developed antispike IgG > 200 BAU/ml (mean, 116.3 [95% CI, 47.04, 287.51] BAU/ml) and 53% showed positive spike-specific T-cellular responses (IFN-gamma release to antigen 1: mean, 0.2 [95% CI, 0.11, 0.31] IU/ml; antigen 2: mean, 0.24 [95% CI, 0.14, 0.37]) after the second vaccination. Conclusions Vaccination with two doses of NVX-CoV2373 was able to elicit a SARS-CoV-2-specific immune response in pwMS lacking adequate immune responses to previous mRNA/viral vector vaccination. For patients receiving S1PR modulators, an increase in anti-SARS-CoV-2 IgG antibodies was detected after NVX-CoV2373 vaccination, whereas in ocrelizumab-treated patients, the increase of antiviral T-cell responses was more pronounced. Our data may impact clinical decision-making by influencing the preference for NVX-CoV2373 vaccination in pwMS receiving treatment with S1PR modulation or anti-CD20 treatment.